Rusty Hungary: New Insights in Brownfield Research - Dannert, Éva; Pirisi, Gábor (European Spatial Research and Policy, 2017)
Spatial development and planning in Hungary bear the marks of the post-socialist transformation. This is also observed in the handling of brownfields which, in the wake of political changes, increased in large numbers. In recent years a lot has happened, but we still know far too little about these areas. The paper focuses on the assessment of the extent of brownfields, their properties and regeneration in Hungary. The survey was based on collection of existing and accessible data at national and regional level, complemented by two personal databases. The study extends beyond the spatial dimension of brownfield sites. The results also emphasize further contexts of brownfield management that are not easily perceptible.